Beta Amyloid Deposition Is Not Associated With Cognitive Impairment in Parkinson's Disease - Melzer, Tracy R.; Stark, Megan R.; Keenan, Ross J.; Myall, Daniel J.; MacAskill, Michael R.; Pitcher, Toni L.; Livingston, Leslie; Grenfell, Sophie; Horne, Kyla-Louise; Young, Bob N.; Pascoe, Maddie J.; Almuqbel, Mustafa M.; et al. (Frontiers in Neurology, 2019)
The extent to which Alzheimer neuropathology, particularly the accumulation of misfolded beta-amyloid contributes to cognitive decline and dementia in Parkinson’s disease is unresolved. Here, we used Florbetaben PET imaging to test for any association between cerebral amyloid deposition and cognitive impairment in Parkinson’s, in a sample enriched for cases with mild cognitive impairment. This cross-sectional study used Movement Disorders Society level II criteria to classify 115 participants with Parkinson’s as having normal cognition (n=23), mild cognitive impairment (n=76), or dementia (n=16). We acquired 18F-Florbetaben (FBB) amyloid PET and structural MRI. Amyloid deposition was assessed between the three cognitive groups, and also across the whole sample using continuous measures of both global cognitive status and average performance in memory domain tests. Outcomes were cortical FBB uptake, expressed in centiloids and as standardized uptake value ratios (SUVR) using the Centiloid Project whole cerebellum region as a reference, and regional SUVR measurements. FBB binding was higher in PDD, but this difference did not survive adjustment for the older age of the PDD group. We established a suitable centiloid cut-off for amyloid positivity in Parkinson’s (31.3), but there was no association of FBB binding with global cognitive or memory scores. The failure to find an association between PET amyloid deposition and cognitive impairment in a moderately large sample, particularly as it was enriched with PD-MCI patients at risk of dementia, suggests that amyloid pathology is not the primary driver of cognitive impairment and dementia in most patients with Parkinson’s.